Diagrammatic representation and inference : 11th International Conference, Diagrams 2020, Tallinn, Estonia, August 24-28, 2020, Proceedings /: 11th International Conference, Diagrams 2020, Tallinn, Estonia, August 24-28, 2020, Proceedings. ([2020]) - Unknown
No abstract available